Six-month clinical outcomes of drug eluting stents in patients with coronary artery disease: an experience in real-world Indian patients - Verma, Gaurav Sardarilal (International Journal of Research in Medical Sciences, 2021)
Background: Treatment of patients with coronary artery disease using drug eluting stents (DES) remains a challenge due to stent thrombosis and in-stent restenosis. The present study sought to investigate the safety and clinical performance of DES in real-world Indian patients with coronary artery disease. Methods: This prospective, non-randomized, single-center study enrolled 114 patients with coronary artery disease who were implanted with DES from January-2005 to September-2007. Clinical and angiographic follow-up were performed at 6 months after the index procedure. The primary endpoints of the study were: (major adverse cardiac events (MACE) defined as a composite of any episode of rest angina, myocardial infarctions (MI), repeat percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery (CABG), or (angiographic restenosis defined as ≥50% diameter stenosis at the treated site at 6-month follow-up. The secondary endpoints of the study were occurrence of any MACE events and stent vessel occlusion during the first 30 postprocedural days. Results: A total of 125 lesions were treated by implantation of 130 DES. Only one patient (0.9%) developed minor bleeding during hospitalization. At the 6-month follow-up, MACE was 10%, including 1 (1.3%) MI, 2 (2.5%) unstable angina, 3 (3.8%) stable angina, 1 (1.3%) repeat PCI, and 1 (1.3%) CABG. Angiographic restenosis was found in 7 (8.8%) patients. Comparison of characteristics between patients with and without angiographic restenosis revealed significant effects of presence of diabetes (p<0.012), hyperlipidaemia (p<0.028), and stent length>20 mm (p<0.05). Conclusions: The study results demonstrated excellent safety and clinical performance of DES in real-world Indian patients with coronary artery disease.